Pengembangan Job Sheet Kendali Mesin Listrik berbasis Variable Frequency Drive di Pendidikan Vokasi - Fitria Anggraini; Aswardi Aswardi (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to produce job sheet learning media that have been tested for feasibility through validity, practicality, and effectiveness tests as a support in the implementation of practicum in the Variable Frequency Drive (VFD)-based Industrial Electrical Machinery Control course. This research was conducted on D4 students in the Industrial Electrical Engineering Department of Electrical Engineering, Padang State University in the Industrial Electrical Machinery Control course. This research phase uses the Research & Development (R&D) method, with the 4-D (Four-D) development model. Research data were obtained from instrument sheets or questionnaires to test validity and practicality, and performance sheets in the form of rubrics to test effectiveness. The data analysis technique in this study is descriptive quantitative. The results of the validity test of the VFD-based Industrial Electrical Machine Control Practicum Jobsheet are declared in the valid category. The results of the job sheet practicality test based on the responses of the Electrical Machine Control Course Lecturer are stated in the very practical category, and the results of the practicality test based on student responses are stated in the very practical category. And the results of the job sheet effectiveness test stated that the job sheet was effective based on the average student learning outcomes in the very good category.